LAYANAN BIMBINGAN KONSELING MELALUI TA’ZIR UNTUK MENINGKATKAN KEDISILINAN SANTRI - Abdul Aziz, Muhammad (AflahConsilia : Jurnal Bimbingan dan Konseling, 2023)
Islamic boarding schools as Islamic educational institutions certainly have efforts to develop students to behave in accordance with Islamic religious values. The Sabilunnajah Simo Islamic Boarding School needs to improve the regulations that must be implemented and obeyed by the students in order to increase the discipline of the students. One of them is the ta'zir effort implemented in Islamic boarding schools. The main purpose of giving ta'zir to students is so that students feel deterred and will not repeat their wrong actions. This research uses qualitative research with a descriptive approach. Data collection was carried out through interviews, observation and documentation methods. The informants that the researchers studied were the head of the Islamic boarding school, security witness administrators, students who had been given ta'ziran and students at the Sabilunnajah Islamic Boarding School. The informants involved were 8 people consisting of 1 Mrs. Nyai, 5 administrators and 2 students. The results of research regarding ta'zir efforts in improving the discipline of female students at the Sabilunnajah Simo Islamic boarding school, it was found that ta'zir efforts are by giving punishment to students who violate, the types of ta'zir come in various forms, the administrators divide ta'zir into 3 categories, namely light, medium and heavy, there are 2 types applied, namely written and physical.